2017
DOI: 10.1080/23328940.2017.1294235
|View full text |Cite
|
Sign up to set email alerts
|

Leptin, adiponectin, and ghrelin responses to endurance exercise in different ambient conditions

Abstract: Excessive positive energy balance is a major factor leading to obesity. The ability to alter the appetite-regulating hormones leptin, adiponectin, and ghrelin may help decrease excessive energy intake. Exercise and exposure to extreme temperatures can independently affect these appetiteregulating hormones. PURPOSE: To determine the effect of exercising in different environmental conditions on the circulating concentrations of leptin, adiponectin, and ghrelin. METHODS: Eleven recreationally-trained male partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…The effect of exercise on plasma ghrelin has previously been investigated mostly in humans using exercise regimens such as treadmill running, cycling, and rowing, and also in a few rodent studies and in some other animal models. While many of these clinical studies and some preclinical studies demonstrated lower plasma ghrelin following exercise [36] , [38] , [39] , [40] , [41] , [42] , [43] , [69] , [70] , higher plasma ghrelin also has been observed [37] , [44] , [45] , [46] , [71] , [72] , [73] , as has unchanged plasma ghrelin [47] , [48] , [74] . The wide range of changes to plasma ghrelin could be due to the differences in the type, intensity, and duration of exercise, the metabolic and age profiles of the study subjects, the blood sample processing (which optimally is performed using a specific regimen to preserve bioactive acyl-ghrelin), and the types of ghrelin (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of exercise on plasma ghrelin has previously been investigated mostly in humans using exercise regimens such as treadmill running, cycling, and rowing, and also in a few rodent studies and in some other animal models. While many of these clinical studies and some preclinical studies demonstrated lower plasma ghrelin following exercise [36] , [38] , [39] , [40] , [41] , [42] , [43] , [69] , [70] , higher plasma ghrelin also has been observed [37] , [44] , [45] , [46] , [71] , [72] , [73] , as has unchanged plasma ghrelin [47] , [48] , [74] . The wide range of changes to plasma ghrelin could be due to the differences in the type, intensity, and duration of exercise, the metabolic and age profiles of the study subjects, the blood sample processing (which optimally is performed using a specific regimen to preserve bioactive acyl-ghrelin), and the types of ghrelin (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of the ghrelin system in mediating exercise capacity and the effects of exercise on food intake, body weight, and blood glucose are of particular interest given the central role of ghrelin in these processes [1] , [12] . The effect of exercise on plasma ghrelin levels has been investigated in multiple human and rodent studies although the results have been inconsistent, demonstrating either a decrease, increase, or no change [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] . Notwithstanding these discrepant observations on the changes in plasma ghrelin with exercise, the impact of the ghrelin system on performance of exercise, food intake after exercise, and, more broadly, the healthy metabolic outcomes of exercise is not well-established.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we have previously reported a significant difference in core body temperature during the final 10 min of the trial. 31 Although this study was unable to find statistical significance in plasma BDNF between trials, we did note an increase in plasma BDNF concentrations following exercise in the heat compared with the other temperatures. The non-statistically significant elevation in BDNF concentrations following the exercise bout in the heat may be related to metabolic energy management strategies adopted to compensate for elevated plasma glucose during exercise in the heat, and suggests that neuronal growth and synapse improvement potential was greatest following the H trial.…”
Section: Discussionmentioning
confidence: 62%
“…The core body temperature data have been previously reported. 31 The food bars consist of 4 g fat, 2 g protein, 29 g carbohydrates, and 9 g of dietary fiber. To ensure dietary intake was not responsible for any variation in dose response, the same bar was ingested for every bout.…”
Section: Experimental Trialsmentioning
confidence: 99%
“…In the study conducted by Kim et al, serum leptin levels had a significant relationship with FEV1, but not with FVC and FEF 75% and PC20 in all subjects (13). Lack of physical exercise is one of risk factors which resulted in obesity and inflammation status (14). Heiniger et al demonstrated that body mass index (BMI) was used to classify patients in earlier studies.…”
Section: Additionally An Association Was Observed Betweenmentioning
confidence: 99%